The evolution of surface magnetic fields in young solar-type stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Folsom, C. P.; Petit, P.; Bouvier, J.; Donati, J.-F.; Morin, J.
Abstract: The surface rotation rates of young solar-type stars decrease rapidly with age from the end of the pre-main sequence though the early main sequence. This suggests that there is also an important change in the dynamos operating in these stars, which should be observable in their surface magnetic fields. Here we present early results in a study aimed at observing the evolution of these magnetic fields through this critical time period. We are observing stars in open clusters and stellar associations to provide precise ages, and using Zeeman Doppler Imaging to characterize the complex magnetic fields. Presented here are results for six stars, three in the in the β Pic association (~10 Myr old) and three in the AB Dor association (~100 Myr old).